2009
DOI: 10.1016/s2255-4971(15)30069-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Results Achieved in Anterior Cruciate Ligament Reconstruction With Two Kinds of Autologous Grafts: Patellar Tendon Versus Semitendinous and Gracilis

Abstract: Objective: this study aims to compare the arthrometric and isokinetic examination results from two types of autologous grafts: the central third of the patellar ligament and a graft formed by the tendons of the semitendinosus and gracilis muscles, within the same rehabilitation protocol, six months after the surgery. Methods: the results from examinations carried out on 63 patients were analyzed. These patients were divided in two groups: one group of 30 patients who received a patellar tendon graft and anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…2 Although several methods of ACL reconstruction exist, the two most common are bone-patellar tendon-bone (BTB) reconstruction using an autograft of the middle third of the patellar tendon and reconstruction using a hamstring tendon (HT) graft. [3][4][5][6][7][8] Although previous well-designed studies have compared the outcomes of these two techniques, even with a long follow-up period, any comparison is complicated by the use of different surgical techniques and graft stabilization procedures. [3][4][5][6][7][8] In our institution, the standard stabilization method for both BTB and HT grafts incorporates titanium interference screws.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although several methods of ACL reconstruction exist, the two most common are bone-patellar tendon-bone (BTB) reconstruction using an autograft of the middle third of the patellar tendon and reconstruction using a hamstring tendon (HT) graft. [3][4][5][6][7][8] Although previous well-designed studies have compared the outcomes of these two techniques, even with a long follow-up period, any comparison is complicated by the use of different surgical techniques and graft stabilization procedures. [3][4][5][6][7][8] In our institution, the standard stabilization method for both BTB and HT grafts incorporates titanium interference screws.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be rational to make patients undergoing ACL reconstruction fill SF-36 forms, to correlate their scores with that of other tests, and be able to confirm our results. Literature and meta-analysis studies 10,[20][21][22] have shown significant isokinetic strength losses in extensor (quadriceps) muscles in patellar groups, especially at an angular velocity of 180 degrees/s. However, this difference has not been consistently found in other meta-analysis studies.…”
Section: Discussionmentioning
confidence: 99%
“…This return to the old technique was only possible through advances in anatomy and biomechanics, along with arthroscopy using new tools and fixation techniques which provide earlier rehabilitation and better results. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Improvements and innovations in ACL reconstruction techniques have produced satisfactory results for instability control and early return to sports. 3 , 18 …”
Section: Discussionmentioning
confidence: 99%